Pancreatic Langerhans cell histiocytosis in a cat. (November 2019) - Rissi, Daniel R.; Brown, Cathy A.; Gendron, Karine; Good, Jennifer; Lane, Selena; Schmiedt, Chad W.
In contrast to pulmonary Langerhans cell histiocytosis (LCH), which is a proliferative disorder of Langerhans cells that affects the lungs and other organs of cats, LCH involving a single organ system has not been documented in cats, to our knowledge. Herein we describe a case of pancreatic LCH in a 9-y-old castrated male Domestic Shorthaired cat that was evaluated for possible renal transplantation. The cat was hypoglycemic, hyperinsulinemic, and azotemic. Ultrasound examination revealed a diffusely enlarged, normoechoic pancreas. The cat was euthanized because of severe renal azotemia and the possibility of pancreatic neoplasia. Grossly, the pancreas was enlarged, and both kidneys were pale white, firm, and had irregular capsular surfaces. Histologically, the pancreas was expanded with interlobular, intraparenchymal, and ductal clusters of round-to-polygonal cells admixed with fibrous connective tissue and scattered lymphocytes. Infiltrating cells had a moderate amount of eosinophilic cytoplasm, round-to-indented nuclei with finely stippled chromatin and 1 or 2 nucleoli, and were strongly immunoreactive for CD18, ionized calcium-binding adapter molecule 1, and e-cadherin. The morphologic and immunohistochemical features of the pancreatic changes were consistent with single-system LCH.